The Effect of Parental Income and Level of Trust in Using Online Stock Investment Applications on Gen Z Investment Decisions in DKI Jakarta - Sekar Mustika Pangesthi; Indianik Aminah (Indonesian Journal of Entrepreneurship and Startups, 2024)
KSEI data (2024) shows that the number of investors in the capital market is dominated by investors under 30 years old. At the age of 20-27 years, it is suspected that the existence of parental income in a person's financial decisions is still very large. The level of trust in investment applications is also thought to be a consideration in investment decisions in Generation Z. The sample in this study was 110 respondents who were Generation Z aged 20-27 years in DKI Jakarta. This study is a quantitative study analyzed using SmartPLS version 4. The results of the research test, the t-statistic value of 1.954 and the p-value of 0.026 and the original positive sample of 0.147 indicate that parental income has a positive and significant effect on stock investment decisions. The second hypothesis, the t-statistic of 12.020 and the p-value of 0.000 and the original positive sample of 0.709 indicate that the level of trust in the use of stock investment applications has a positive and significant effect on stock investment decisions. The third hypothesis, it can be seen that based on the simultaneous F test calculation, the F-count value of 82.29> F-table 3.08, which means that the parental income variable and trust in the use of stock investment applications have a simultaneous effect. This study has implications for Generation Z to properly manage their finances to be invested in reputable investment platforms, and for the government to eradicate fraudulent investments.